Kearifan Lokal Masyarakat Dalam Pemanfaatan Pohon Enau di Desa Siberakun Kecamatan Benai Kabupaten Kuantan Singingi - Memi Yuldiati; Zulfan Saam; Mubarak Mubarak (Universitas Riau, 2016)
Every society having different local wisdom, including in the use of trees, lands, forest, lake and river. The village society Siberakun process palm tree with utilize water nira to produced into palm sugar. This research aims to know the forms of local wisdom Siberakun in the use of palm tree and environmental aspects and to know economic value of palm sugar craftman.This research is a qualitative research by using case study method, Data were collected by observation, documentation and interview with key informants are palm craftmans. Research results are as follows : The form of laocal wisdom society in making use of palm tree is : 1). A craftman used traditional instrument and can be update so can not caused negative impact for the environment like the stairs from wood, fuel use wood, mold sugar made of board, and packing palm sugar using banana leaf, 2). People have local knowledge in determining when a palm sugar paste ready to printed, 3). Waste resulting from firewood can be used to ash rub and fertilizer, 4). People have local knowledge for make fragrant palm sugar is squeeze the leaves or young mangosteen bark mixed lime betel which is an ingredient organic that does not contain a hazardous chemicals, 5). existencepalm trees the river to disproved abrasion and erosion. The palm tree reserving biological resources civet as cause the growth of palm tree naturally. The obtacles in process nira into palm sugar are difficult to processing or clean up the trees and other job more promising such as tapping rubber and rubber plantation business.